Sustainable Cultural Tourism Development in Tamkesi Traditional Village: Findings from the 6A Framework Analysis - Apryanto Gebyanus Putra Haukilo; Aplonia Pala; Nikolaus Uskono; Yohanes Fritantus; Hendrikus Hironimus Botha; Theodecilda Bimolo (International Journal of Research and Community Empowerment, 2026)
Cultural tourism in traditional Indonesian villages holds significant potential for preserving cultural heritage while driving local economic growth. Tamkesi Traditional Village in North Central Timor, East Nusa Tenggara, is one of the most iconic heritage sites with unique architecture and cultural traditions. This study aims to analyze the development of cultural tourism in Tamkesi using the 6A tourism framework, namely Attractions, Amenities, Supporting Services, Activities, Accessibility, and Available Packages, and collaborative governance principles. A qualitative descriptive approach was used, involving in-depth interviews with local stakeholders, direct observation, and document analysis. The findings indicate that despite Tamkesi’s strong appeal and cultural authenticity, its tourism development faces limitations in amenities, accessibility, supporting services, and structured tour packages. Collaborative governance among local communities, government agencies, and tourism actors is identified as a crucial strategy to address these gaps and promote sustainable cultural tourism development. The study concludes that integrated planning and community-based collaboration are essential for strengthening all components of the 6A framework. This research contributes to the achievement of SDG 11 by supporting cultural heritage preservation and sustainable settlements, and to SDG 17 by reinforcing multi stakeholder partnerships to ensure effective and sustainable cultural tourism governance.